Learning Approaches in Dental Students: An Instrumental and Profiles Analysis - Mendel, Nancy Beatriz (2024)
Students' learning approaches are described as different modes, procedures, or strategies that students use to process the information they need to learn. This paper analyzes the learning approaches in students of Dentistry using the Revised Two Factor Study Process Questionnaire (R-SPQ-2F). It is proposed, on the one hand, to analyze the internal structure of the instrument, and on the other, to examine approaches to students and their relationship to academic performance. 752 dental students participated. As a result, adequate evidence of the instrument's internal validity was obtained -confirmatory factor analysis, internal consistency, and factorial invariance analysis. Besides, a latent profile analysis obtained two learning approach profiles. One profile, with a deep approach over the surface, and the other, with similar levels of both. Then an analysis of average differences found that students who mostly employ the deep approach have higher academic performance than those with similar levels of both approaches. These results show that while it is important to promote the adoption of the deep approach in students, it is necessary to consider both -deep and surface-, as they are not exclusive. Although learning approaches are measured independently, in practice students combine features of both by forming their learning profiles.